2008
DOI: 10.1093/ejo/cjn018
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the duration of orthodontic treatment: a systematic review

Abstract: The aim of this study was to systematically investigate the literature for articles referring exclusively to the duration of orthodontic therapy and to explore the various factors that could affect this. A Medline search from 1990 to the first week of March 2005 was conducted, the Cochrane Database for Systematic Reviews was utilized, five orthodontic journals were hand searched, the abstracts of related articles were reviewed to search for any relevant studies that might have been missed, and the reference li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
125
3
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(181 citation statements)
references
References 39 publications
7
125
3
13
Order By: Relevance
“…Furthermore, the MB-treatment should have lasted for at least one year as this represents a normal average duration for a MB-treatment according to literature (Richmond et al, 1993;Teh et al, 2000;Mavreas et al, 2008). It was also considered, that the retention period should have lasted for at least one year, because it has been shown that most remineralization procedures take place during the first six months after treatment and beyond one year no major changes are seen (Fehr et al, 1970;Artun and Thylsturp, 1989).…”
Section: Sign-test For Wsl Changed Teeth T2mentioning
confidence: 99%
“…Furthermore, the MB-treatment should have lasted for at least one year as this represents a normal average duration for a MB-treatment according to literature (Richmond et al, 1993;Teh et al, 2000;Mavreas et al, 2008). It was also considered, that the retention period should have lasted for at least one year, because it has been shown that most remineralization procedures take place during the first six months after treatment and beyond one year no major changes are seen (Fehr et al, 1970;Artun and Thylsturp, 1989).…”
Section: Sign-test For Wsl Changed Teeth T2mentioning
confidence: 99%
“…7,13 Many studies have been conducted on malocclusion classification and have reported that the duration of treatment generally differed depending on the treatment approach. [13][14][15][16] However, studies that compared the duration of treatment on the basis of Angle classifications were usually poster abstracts presented at conferences and there were no detailed studies available. In this study, the average treatment period for 387 patients was found as 27.8 months.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have conferred that treatments with extraction lasted longer than those without extraction, and single-phase treatments shorten the duration of treatment. 13,16 Furthermore, independent of the malocclusion, the existence of a unilaterally or bilaterally impacted canine could lengthen the duration of the treatment. 20,21 As per such examples and the findings of this study, it could be determined that a pricing solely based on classification is not sufficient, or fair, with respect to the labor/cost balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 The reasons cited to be because of decreased vascularity and low cellular response for OTM. 20 …”
mentioning
confidence: 99%